Catheterization of post infection parotid duct sialocele with paediatric Ryles tube: A case report - Parul Tandon; Harish Saluja; Seemit Shah; Anuj Dadhich; Shivani Sachdeva (Journal of Oral Biology and Craniofacial Research)
Sialocele is a cavity filled with saliva, usually as a result of trauma, complication of surgery, sialolithiasis or bacterial infection residing inside the duct. Many cases of parotid sialocele have been reported in the literature, but only very few cases of parotid duct sialocele have been reported. We report a case of an unusual facial swelling over buccal mucosa at the route of Stenson’s duct with poor oral hygiene, a case of parotid duct sialocele with secondary infection and describe its diagnosis and management.